Utilizing TikTok in Enhancing Language Abilities: A Literature Review - Tamaño, Lexxus Dominic (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This literature review examines the potentials and challenges of using TikTok as a pedagogical tool for enhancing language abilities. Drawing from studies published between 2019 and 2025, it presents research-based insights into how TikTok promotes engagement, creativity, and communication in language classrooms. The review also highlights limitations such as distraction, limited instructional depth, and the need for structured integration. Overall, this paper aims to provide educators and learners with a clearer understanding of how TikTok can be effectively utilized to support language teaching and learning. The findings suggest that while TikTok offers a highly engaging, authentic platform for practical language use and cultural exposure, its success is heavily dependent on a deliberate instructional design that mitigates distractions and integrates short-form content into broader curriculum goals. Ultimately, this review advocates for a balanced and informed approach to leveraging this popular social media platform for modern language education.